2021
DOI: 10.1097/hjh.0000000000002948
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-producing adenoma-harbouring KCNJ5 mutations is associated with lower prevalence of metabolic disorders and abdominal obesity

Abstract: Yen-Hung Lin g , on behalf of the TAIPAI Study Group Objective: Aldosterone overproduction and lipid metabolic disturbances between idiopathic hyperaldosteronism (IHA) and unilateral aldosterone-producing adenoma (APA) have been inconsistently linked in patients with primary aldosteronism. Moreover, KCNJ5 mutations are prevalent among APAs and enhance aldosterone synthesis in adrenal cortex. We aimed to investigate the prevalence of metabolic syndrome (MetS) in each primary aldosteronism subtype and observe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The mechanism of aortic calcification formation is complex and involves multifactorial vascular inflammation ( 40 ). In our prior study we investigated serum CRP levels in PA patients, and showed that KCNJ5 mutations were associated with lower levels of pro-inflammation factors ( 41 ), metabolic syndrome and abdominal obesity ( 42 ). This may explain why the patients without KCNJ5 somatic mutations had a higher burden of aortic calcified plaques despite lower blood pressure and less severe aldosteronism compared to those with KCNJ5 somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of aortic calcification formation is complex and involves multifactorial vascular inflammation ( 40 ). In our prior study we investigated serum CRP levels in PA patients, and showed that KCNJ5 mutations were associated with lower levels of pro-inflammation factors ( 41 ), metabolic syndrome and abdominal obesity ( 42 ). This may explain why the patients without KCNJ5 somatic mutations had a higher burden of aortic calcified plaques despite lower blood pressure and less severe aldosteronism compared to those with KCNJ5 somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…No differences existed between the two subtypes in terms of TC and FBG levels among non‐Asian patients with PA. We supposed the different lifestyles play an important part. In addition, KCNJ5 mutation, prevalent in APA patients of Asian ethnicity, 42 might matter. According to Chen et al., 42 IHA patients exhibited significantly higher TG levels than APA patients with KCNJ5 mutations but showed no difference compared with those without KCNJ5 mutations, which is in accordance with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KCNJ5 mutation, prevalent in APA patients of Asian ethnicity, 42 might matter. According to Chen et al., 42 IHA patients exhibited significantly higher TG levels than APA patients with KCNJ5 mutations but showed no difference compared with those without KCNJ5 mutations, which is in accordance with our results. Given the relatively small number of studies included in each subgroup, additional research should be conducted to validate it.…”
Section: Discussionmentioning
confidence: 99%
“…This change may be driven by the decline of renal function after treatment of PA, which would lead to a decrease of lipoprotein lipase and hepatic triglyceride lipase and interfere with the metabolism of lipids (110). As for KCNJ5 mutation, the previous study revealed only patients with mutations had a significant increase of TG after adrenalectomy, but not in patients without mutations (103).…”
Section: Relationships Of Kcnj5 Somatic Mutations With Metabolic Diso...mentioning
confidence: 99%
“…CT is a well-established imaging tool to quantify abdominal adipose tissue, utilizing the Hounsfield Units (HU) range to measure the subcutaneous and visceral fat areas (102). Concerning the effect of KCNJ5 somatic mutations on MetS, Chen et al first reported that APA patients with KCNJ5 mutations had fewer MetS, lower triglyceride (TG) levels, waist circumference, and subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) area than those without KCNJ5 mutations even after matching for age (103). APA patients with KCNJ5 mutations also had fewer MetS and lower triglyceride levels compared to patients with BAH.…”
Section: Relationships Of Kcnj5 Somatic Mutations With Metabolic Diso...mentioning
confidence: 99%